Turnover intention and its antecedents: The mediating role of work–life balance and the moderating role of job opportunity - Ahmad Saufi, Roselina; Aidara, Samsidine; Che Nawi, Noorshella Binti; Permarupan, P. Yukthamarani; Zainol, Noor Raihani Binti; Kakar, Abdul Samad (Frontiers in Psychology, 2023)
Due to the higher attrition rate in higher education institutions (HEIs), the attraction and retention of top talents in higher education have become a challenge for human resource (HR) professionals. The primary area of discussion among business executives and HR professionals is how top talent can be retained and maintained. Thus, the purpose of this study is to examine the impact of human resource management practises (HRMPs), oraganisational reputation (OGR), occupational prestige (OPP) and work–life balance (WLB) on turnover intention (TOI) of the academics working in HEIs. The study also aims to examine WLB as a mediator and job opportunity (JBO) as a moderator of the relationships mentioned above. Data collected through an online survey from 466 respondents were analysed using partial least square structural equation modelling. The findings of the study showed that OGR, OPP and WLB were negatively related to TOI. However, the impact of HRMPs on TOI was not direct; instead, it was mediated by WLB. The findings also demonstrated that WLB significantly mediated the relationship between OGR and OPP. Furthermore, the results also confirmed that JBO significantly moderated the relationship between WLB and TOI. The findings of the study provide guidelines for a comprehensive retention strategy and a holistic model of academics TOI that can assist HR professionals, policymakers and management in developing an effective strategic recruitment and retention plan.